Cyber Efficiency and Cyber Resilience: Complementary objectives competing for the same resources. - Linkov, Igor; Ligo, Alexandre; Stoddard, Kelsey; Perez, Beatrice; Strelzoff, Andrew; Bellini, Emanuele; Kott, Alexander (Communications of the ACM, 2023)
This article reports on the paired objectives of cyber efficiency and cyber resilience in evaluating how successful a digital system will be in accomplishing its functions, where efficiency in this context is defined as the ability to function successfully without waste and resilience is the ability of a system to deal with disruptive events. Topics include the interplay between cyber efficiency and cyber resilience, with a look at both short-term efficiency and long-term efficiency, and an illustration of these objectives looking at the WannaCry ransomware and the National Health Service in England. [EPC]